Probing the Fen +/Fe(N-1)+ Redox Potential of Fe Phthalocyanines and Fe Porphyrins as a Reactivity Descriptor in the Electrochemical Oxidation of Cysteamine - Paez-Collio, M; Paez-Collio, M; Zagal-Moya, J; Zagal-Moya, J; Silva-Gonzalez, N; Silva-Gonzalez, N; Oyarzun-Medina, M; Oyarzun-Medina, M (ELSEVIER SCIENCE SA, 2018)
The Mn +/M(n - 1)+ redox potential of MN4 macrocyclic molecular catalysts is a very good reactivity descriptor for several electrochemical reactions. One important feature about this reactivity descriptor is that it can be determined experimentally under the same conditions of the kinetic measurements in contrast to other descriptors like intermediate binding energies that are estimated from DFT calculations. However a linear correlation between both descriptors seems to exist. Plots of activity as (logj)(E) at constant E versus the Mn +/M(n - 1)+ redox potential gives volcano correlations. Another important aspect about this parameter is that it is possible to tune the Mn +/M(n - 1)+ redox potential of the MN4 catalyst by manipulating the structure of the macrocyclic complex and tailoring the electron-withdrawing power of the ligands to obtain the maximum activity. In this work we have probed the redox potential as a reactivity descriptor for the oxidation of cysteamine studying a series of substituted Fe phthalocyanines and Fe porphyrins adsorbed on glassy carbon and pyrolytic graphite in alkaline media. As expected the catalytic activity of these FeN4 species varies strongly with the Fe (II)/(I) redox potential of the different Fe phthalocyanines and a plot of activity as (logj)(E) versus E degrees Fe(II/I) gives a volcano shaped correlation so a formal potential value exists for which the highest activity can be achieved demonstrating that the formal potential of the complexes seems to be an universal reactivity descriptor for electrochemical reactions.